Children's Early Awareness of Comprehension as Evident in Their Spontaneous Corrections of Speech Errors. Issue 1 (9th June 2017) - Wellman, Henry M.; Song, Ju‐Hyun; Peskin‐Shepherd, Hope
Abstract : A crucial human cognitive goal is to understand and to be understood. But understanding often takes active management. Two studies investigated early developmental processes of understanding management by focusing on young children's comprehension monitoring. We ask: When and how do young children actively monitor their comprehension of social‐communicative interchanges and so seek to clarify and correct their own potential miscomprehension? Study 1 examined the parent–child conversations of 13 children studied longitudinally in everyday situations from the time the children were approximately 2 years through 3 years. Study 2 used a seminaturalistic situation in the laboratory to address these questions with more precision and control with 36 children aged 2–3 years.